Diffuse intestinal ganglioneuromatosis in a child - Matthews, Mika A.B. (2013)
A 7 year old male with a history of congenital neutropenia and growth hormone deficiency presented with abdominal pain, fevers, and diarrhea. Imaging and endoscopy revealed significant inflammation of the ascending colon with stenosis at the level of the hepatic flexure. A right hemicolectomy was performed, and pathologic findings were consistent with diffuse intestinal ganglioneuromatosis. Due to recurrent mass effect at the intestinal anastomotic site detected radiologically, a second intestinal resection was performed 7 months later. Genetic testing was negative for mutations in the RET protooncogene, NF1 and PTEN tumor suppressor genes. We report a case of diffuse intestinal ganglioneuromatosis in a child with congenital neutropenia.